Personal protective equipment for surgeons during COVID-19 pandemic: systematic review of availability, usage and rationing. Issue 10 (24th August 2020) - Jessop, Z M; Dobbs, T D; Ali, S R; Combellack, E; Clancy, R; Ibrahim, N; Jovic, T H; Kaur, A J; Nijran, A; O'Neill, T B; Whitaker, I S
Abstract: Background: Surgeons need guidance regarding appropriate personal protective equipment (PPE) during the COVID-19 pandemic based on scientific evidence rather than availability. The aim of this article is to inform surgeons of appropriate PPE requirements, and to discuss usage, availability, rationing and future solutions. Methods: A systematic review was undertaken in accordance with PRISMA guidelines using MEDLINE, Embase and WHO COVID-19 databases. Newspaper and internet article sources were identified using Nexis. The search was complemented by bibliographic secondary linkage. The findings were analysed alongside guidelines from the WHO, Public Health England, the Royal College of Surgeons and specialty associations. Results: Of a total 1329 articles identified, 95 studies met the inclusion criteria. Recommendations made by the WHO regarding the use of PPE in the COVID-19 pandemic have evolved alongside emerging evidence. Medical resources including PPE have been rapidly overwhelmed. There has been a global effort to overcome this by combining the most effective use of existing PPE with innovative strategies to produce more. Practical advice on all aspects of PPE is detailed in this systematic review. Conclusion: Although there is a need to balance limited supplies with staff and patient safety, this should not leave surgeons treating patients with inadequate PPE. Graphical Abstract: This systematic review provides a comprehensive overview of all the issues surrounding personal protective equipment for surgeons during the COVID-19 pandemic. To overcome this global challenge needs an evidence-based, collaborative, innovative multidisciplinary approach. Better to be safe than sorry